Parent–Child Discrepancy on Children’s Body Weight Perception: The Role of Attachment Security - Uccula, Arcangelo; Nuvoli, Gianfranco (Frontiers in Psychology, 2017)
The discrepancies between parents and their children on the description of the behavior and representations of their children have been shown in various studies. Other researchers have reported the parents’ difficulty in correctly identifying the weight status of their children. The purpose of our study was to investigate the parent's attributional accuracy on their children's body weight perception in relation to the children attachment security. It was hypothesized that insecure children's parents have a greater discrepancy with their children compared to secure children with their parents. The research participants were 217 children, aged between 5 and 11 years of both genders, and their parents. The attachment pattern was measured by the SAT of Klagsbrun and Bowlby, with the Italian version of Attili. The children were also shown a set of figure body-drawings with which to measure the perception of their weight status. Parents answered a questionnaire to find out the parental attribution of their children's perception. The results show that the body weight perception of insecure children's parents have a greater discrepancy with their children’s body weight perception compared with parentally secure children. In particular, parents of insecure children tend to underestimate the perception of their children. This result is most evident in disorganized children. In addition, the perception of insecure children’s parents show a greater correlation with children’s actual weight rather than with their children's perception. These results suggest that the discrepancies on the perception of children's body weight between parents and children may be influenced by the poor parental attunement to their children's internal states, which characterizes the insecure parent-child attachment relationship.